Innovative control of fruit fly (Bactrocera dorsalis) on tomato plants (Solanum lycopersicum) using the push-pull technique for sustainable food security - Hulwani, Najwa Zati; Hestriyasha, Adira; Valentina, Angela (Journal of Agrosociology and Sustainability, 2025)
Background: Pesticide residues in tomato (Solanum lycopersicum) cultivation pose serious health and environmental risks, exacerbated by the excessive use of synthetic pesticides to control fruit fly pests (Bactrocera dorsalis). This review aims to evaluate the push-pull technique an integrated pest management strategy using repellent plants like lemongrass (Cymbopogon nardus) and attractant plants such as basil (Ocimum basilicum), supported by yellow sticky traps as a sustainable solution for fruit fly control. Methods: This systematic literature review was conducted by screening 1,300 articles from scientific databases within the last 10 years using PRISMA guidelines, from which 4 studies were ultimately selected for qualitative synthesis. Findings: Based on the analysis of secondary literature, the synthesis of results shows that lemongrass releases volatile compounds capable of suppressing fruit fly populations by up to 40-60%, while basil and yellow sticky traps effectively lure fruit flies away from the main crop and can reduce infestation rates by 35-55%. This combination effectively suppresses pests, reduces dependency on chemical pesticides, and supports food security by stabilizing production. Conclusion: It should be noted that these findings are derived from a narrative data synthesis of secondary literature, not primary field trials, and this review does not include a quantitative meta-analysis to statistically measure the combined effect. This study concludes that the wider adoption of the push-pull system, coupled with farmer training and technological integration, offers an eco-friendly and efficient alternative for horticultural pest management. Novelty/Originality of this article: The novelty/originality of this article lies in systematically reviewing the push-pull technique combining lemongrass, basil, and yellow sticky traps as an eco-friendly integrated strategy for controlling tomato fruit fly pests.